Analysis of The Water And Air Police (Polairud) Patrols of Dumai Police Resort In Preventing Maritime Crime - Zatira Rahma Azalia; Riky Novarizal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Indonesia, as the world’s largest archipelagic state, faces significant maritime security challenges, particularly in strategic areas such as Dumai waters bordering the Malacca Strait, highlighting the urgency of strengthening patrol strategies to prevent maritime crimes such as illegal fishing, smuggling, and shipping-related offenses. This study aims to analyze the effectiveness of patrols conducted by the Water and Air Police (Polairud) of Dumai Police Resort in preventing maritime crime using the perspective of Situational Crime Prevention (SCP). This research employs a qualitative method with a descriptive approach and a case study design, with data collected through interviews, observations, and documentation involving purposively selected informants, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that Polairud patrols have effectively implemented SCP strategies, including target hardening, access control, increasing the risk, reducing rewards, and removing excuses, which have contributed to reducing opportunities for maritime crime, although challenges remain such as the vast surveillance area and evolving criminal patterns. In conclusion, Polairud patrols in Dumai play a significant role in maritime crime prevention, but require further enhancement through technological support, stronger inter-agency coordination, and more adaptive strategies, and future research is recommended to explore the integration of surveillance technology and cross-sector collaboration in strengthening maritime security.